2022
DOI: 10.1039/d1ra09098d
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DNA-mediated formation of a porous Cu2(OH)PO4/Co3(PO4)2·8H2O rolling pin shape bifunctional electrocatalyst for water splitting reactions

Abstract: Among the accessible techniques, the production of hydrogen by electrocatalytic water oxidation is the most established process, which comprises oxygen evolution reaction (OER) and hydrogen evolution reaction (HER).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…Thus, it is of prime significance to plan financially savvy and profoundly productive OER electrocatalysts with lesser overpotential and Tafel slopes. 7,8 As of late, a few examinations have shown that layered 9−11 and lithiated 12,13 spinel-type materials are dynamic for the OER in antacid electrolytes. Among the announced electrocatalyst materials, spinel LiMn 1.5 Ni 0.5 O 4 14−21 is of incredible interest because of its structure-dependent redox reaction and phase transformation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is of prime significance to plan financially savvy and profoundly productive OER electrocatalysts with lesser overpotential and Tafel slopes. 7,8 As of late, a few examinations have shown that layered 9−11 and lithiated 12,13 spinel-type materials are dynamic for the OER in antacid electrolytes. Among the announced electrocatalyst materials, spinel LiMn 1.5 Ni 0.5 O 4 14−21 is of incredible interest because of its structure-dependent redox reaction and phase transformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The anodic oxygen evolution reaction (OER, 4OH – → O 2 + 2H 2 O + 2e), as one of the significant half-reactions of water splitting, has attracted enormous research interest as a result of the potential as an effective energy conversion and storage technology with high efficiency and low cost. Although noble metals, like RuO 2 /IrO 2 OER, have been proven for the state-of-the-art electrocatalyst, their expensiveness and the terrestrial scarcity of these valuable metal-based electrocatalysts seriously impede their large-scale applications. Thus, it is of prime significance to plan financially savvy and profoundly productive OER electrocatalysts with lesser overpotential and Tafel slopes. , As of late, a few examinations have shown that layered and lithiated , spinel-type materials are dynamic for the OER in antacid electrolytes. Among the announced electrocatalyst materials, spinel LiMn 1.5 Ni 0.5 O 4 is of incredible interest because of its structure-dependent redox reaction and phase transformation .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental degradation and energy crises due to the overburning of fossil fuels for sustainable progress are major concerns these days. , To address these issues, various technologies, such as CO 2 reduction, methanol oxidation, , rechargeable metal–air batteries, , and water electrolysis, have been developed to date to convert and store green energies. Among them, an important oxygen evolution reaction (OER) process occurring on the anode for energy conversion systems follows the dawdling dynamics due to the involvement of 4OH – and 4e – transfer processes, which due to high overpotential reduces energy efficiency. , Therefore, there is a compelling need for electrocatalysts to accelerate this process.…”
Section: Introductionmentioning
confidence: 99%
“…Nafion is a commonly used binder that shows poor conductivity toward the transport of hydroxide ions, , resulting in the swelling of catalytically active sites, and hence can poison the activity of the catalyst . Recently, a few groups have demonstrated the employment of metal catalysts incorporated with DNA for water splitting electrocatalysis, , methanol oxidation, oxygen evolution reaction, and electrocatalytic water oxidation without using an external binder. , Binding DNA with metal nanostructures provides stability to catalysts when stored in a refrigerator. Additionally, the existence of phosphate backbones in the DNA scaffold results in enhanced activity from the viewpoint of OER.…”
Section: Introductionmentioning
confidence: 99%